Polyaniline (PANI)-Co0.5Mn0.5Fe2O4 nanocomposite: Synthesis, characterization and magnetic properties evaluation - Sozeri, H.; Kurtan, U.; Topkaya, R.; Baykal, A.; Toprak, M. S. (Elsevier Sci Ltd, 2013)
Polyaniline (PANI)/Cobalt-manganese ferrite, (PANI)/Co0.5Mn0.5Fe2O4, nanocomposite was synthesized by oxidative chemical polymerization of aniline in the presence of ammonium peroxydisulfate (APS). Microwave assisted synthesis method was used for the fabrication of core CoFe2O4 nanoparticles. The structural, morphological, thermal and magnetic properties of the nanocomposite were investigated in detail by X-ray diffraction (XRD), fourier-transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM) and vibrating sample magnetometer (VSM). The average crystallite size of (PANI)/Co0.5Mn0.5Fe2O4 nanocomposite by the line profile method was 20 +/- 9 nm. The magnetization measurements revealed that (PANI)/Co0.5Mn0.5Fe2O4 nanocomposite has superparamagnetic behavior with blocking temperature higher than 300 K. The saturation magnetization of the composite is considerably low compared to that of CoFe2O4 nanoparticles due to the partial replacement of Co2+ ions and surface spin disorder. As temperature decreases, both coercivity and strength of antiferromagnetic interactions increase which results in unsaturated magnetization of the nanocomposite. (C) 2012 Elsevier Ltd and Teama Group S.r.l. All rights reserved.
Keywords: Magnetic nanomaterials; Coercivity; Superparamagnetism; Polyaniline